Milet, Türkei. Marmorprovenienz und bauwirtschaftliche Paradoxe (nach Vorarbeiten 2018 und 2019) - Toma, Natalia (e-Forschungsberichte des DAI, 2020)
The field activity at Miletus focused on the identification and photographic documentation of the architectural decoration of Late Roman Imperial buildings (Serapeion, Heroon III, Stadion-East Gate, Theatre, Delphinion, and Faustina-Baths) and on investigating the provenance of its building material. Marble samples were subject of analysis including measurements of stable isotopes (δ18O; δ13C) and petrographical (thin sections) and geochemical characterisation (ICP-MS). The results of the statistical analysis of the archaeometrical data reveal the massive use of marmor heracleoticum in Roman Imperial time and lead to a new definition of the isotopic fields of the Miletus quarries. With regard to the dynamics of the building economy a paradoxical situation can be determined, as certain building sites like the Roman theatre make extensive use of the most expensive white-grey marble in Roman marble trade (Heracleotic marble) along with the massive employment of the fairly propitiously spoliated architecture.